2018
DOI: 10.4067/s0718-95162018005003001
|View full text |Cite
|
Sign up to set email alerts
|

Foliar 2,3-dihydroporphyrin iron (III) spray confers ameliorative antioxidation, ion redistribution and seed traits of salt-stressed soybean plants

Abstract: Dihydroporphyrin iron (III) chelates (also known as DHFe) have a role in plant growth regulation under normal and stressful conditions. In the present study, using Glycine max cultivars Jackson (the salt-sensitive) and Lee68 (the salt-tolerant) as the experimental materials, the physiological and molecular events contributing to the ameliorative effects of foliar DHFe spray on seedling growth; leaf photosynthetic parameters; reactive oxygen species (ROS) content; antioxidant enzyme activity; Na + , K +, and Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The yearly worldwide monetary loss resulting from salinity is 27.5 billion USD [ 1 ]. The decline in crop yield under salt stress was indicated previously by Farouk and Al-Amri [ 3 ], and support the results of the current investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The yearly worldwide monetary loss resulting from salinity is 27.5 billion USD [ 1 ]. The decline in crop yield under salt stress was indicated previously by Farouk and Al-Amri [ 3 ], and support the results of the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity is the foremost global ecological constraint to worldwide sustainable production and food security. Salt stress influences about 936 Mha of arable lands, causing yearly worldwide monetary losses of 27.5 billion USD [ 1 , 2 ]. Severe salinity induces different physio-biochemical abnormalities, including dual hyperosmotic effects, nutritional imbalance, specific ion toxicity, impaired gas exchange, disturbing water homeostasis, or a mixture of these factors, which reduce plant growth and yield [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…K + accumulation in root cells controls the osmotic potential and maintains water equilibrium inside the plant tissue and declines the physiological drought stress induced by salinity (Grattan and Grieve 1998). In sensitive varieties, the over-production of MDA under salinity reflects in high-ROS-molecules generation and the inactivation or low efficiency of antioxidant systems (Farhodi 2011;Cao et al 2018). The plants' ability to scavenge free radicals is quite dependent upon the activity of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition with micro-elements improves the plant's productivity and helps tolerate stressful environments (Hendawy and Khalid 2005). Cao et al (2018) reported that foliar dihydroporphyrin iron (III) chelates spray improved antioxidant capacity and ion redistribution in salt-stressed soybean plants. Torabian et al (2017) reported that sunflower plants cultivated under salinity and foliar sprayed with nano-Fe had increased height and biological yield.…”
Section: Introductionmentioning
confidence: 99%